Adaptive Reuse Study on Balai Kota Cirebon for Sustainable Heritage Conservation - Mahendra, Seto Maulana; Nuryanto, Nuryanto; Permana, Asep Yudi (Proceeding of International Joint Conference on UNESA, 2025)
Balai kota Cirebon as a heritage building is no longer in use. To preserve the existence this building, efforts need to be made to conserve it. One of measures taken to maintain heritage buildings is application of the Adaptive Reuse. This concept can be a viable solution to maintain heritage building and ensure the sustainability of the building. According to the findings of this research, it proposes an idea of transforming function of Balai kota Cirebon into a museum based on analysis of historical value, architectural character, and location. This research aims to determine the conservation methods to be applied in preserving the Balai kota Cirebon. Qualitative descriptive method with a historical approach is utilized in this research. Observations are conducted to investigate building's history. Results of this research can serve as a reference and a standard for success in specific context or application when implementing adaptive reuse on heritage buildings. This building can be transformed into a museum that functions as a place for storing and preserving historical artifacts, a public education center, and supporting further research and studies. Additionally, this museum can enhance cultural awareness and support sustainable tourism development in Cirebon.